The Theological-Academic Resilience of Muhammadiyah in Receiving The Value of The Quran and Hadith During the COVID-19 Pandemic at Al-Azhar University, Egypt - Danarta, Agung; Sayed, Fadwa Aly; Pradana, Mahatva Yoga Adi; Aulia, Aly (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The COVID-19 pandemic was a major challenge for the entire world, prompting varied religious and social reactions among Muslim communities. In Indonesia, Muhammadiyah showed a lively and adaptable response through providing theological guidance, engaging in humanitarian efforts, and transforming education during these difficult times. This study explores how Muhammadiyah students at Al-Azhar University responded to the pandemic, focusing on how they embraced Qur’anic and Hadith values. Using a qualitative, descriptive-interpretive approach rooted in Living Qur’an and Hadith studies, the research gathered data from documentation, observations, and detailed interviews with six key individuals including Indonesian students and leadership at Pimpinan Cabang Istimewa Muhammadiyah Mesir. The results highlight two main ways Muhammadiyah communities received religious messages during the pandemic: exegetical and functional reception. Exegetically, Muhammadiyah tended to focus on Qur’anic verses and Hadiths that view disasters as tests from Allah that call for patience, rational effort, solidarity, and social responsibility rather than seeing them as divine punishment or doom. This interpretation shows Muhammadiyah’s thoughtful approach to Islamic teachings, guided by Manhaj Tarjih, which blends scriptural insights with scientific and humanitarian considerations. Functionally, these religious insights translated into tangible social actions, such as health campaigns, online education, social aid, and organizational efforts coordinated through the Muhammadiyah Covid-19 Command Center (MCCC). Muhammadiyah’s guidance helped Indonesian students in Egypt stay balanced between religious devotion, scientific awareness, and social ethics during the pandemic. Overall, this study enriches Islamic studies, especially Living Hadith studies, modern Islamic jurisprudence, and the understanding of Islamic organizations like Muhammadiyah and Nahdlatul Ulama in their responses to worldwide humanitarian crises.